2017
DOI: 10.1021/acsomega.7b01259
|View full text |Cite
|
Sign up to set email alerts
|

Patterning Metal Nanowire-Based Transparent Electrodes by Seed Particle Printing

Abstract: This article describes a unique combination of inkjet printing of functional materials with an intricate self-assembly process. Gold–silver nanowire (NW) mesh films were produced by a sequential deposition process, in which small metal seed nanoparticle film was deposited at desired areas by inkjet printing, followed by coating with a thin film of NW growth solution. Two different types of NW growth solutions were used: the first, based on benzylhexadecyldimethylammonium chloride, exhibited a bulk solution gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…To improve the wettability of the PDMS, we employed ultraviolet/ozone (UVO) to treat the surface of the cured PDMS. The middle and right panels of 8,57 drop coating, 30 spin coating, 32 spray coating, 43 and Mayer rod coating 13,31 ) and one-step printing methods (ground color of purple) (electrohydrodynamic printing, 49 additive printing, 58 screen printing, 25 inkjet printing, 34 and seed particle printing 59 ), as well as some other transparent conductors (ground color of green) through direct writing of silver nanoparticles (Ag NPs), 60 copper random network, 61 direct printing of Ag precursors, 50 and laser transferring. 51 Note: For the printed Ag NW patterns in the literature, where the transmittance values at the wavelength of 550 nm are not clearly mentioned, the FoMs have been estimated based on the film thicknesses and the physical appearance of the patterns in comparison to our work.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the wettability of the PDMS, we employed ultraviolet/ozone (UVO) to treat the surface of the cured PDMS. The middle and right panels of 8,57 drop coating, 30 spin coating, 32 spray coating, 43 and Mayer rod coating 13,31 ) and one-step printing methods (ground color of purple) (electrohydrodynamic printing, 49 additive printing, 58 screen printing, 25 inkjet printing, 34 and seed particle printing 59 ), as well as some other transparent conductors (ground color of green) through direct writing of silver nanoparticles (Ag NPs), 60 copper random network, 61 direct printing of Ag precursors, 50 and laser transferring. 51 Note: For the printed Ag NW patterns in the literature, where the transmittance values at the wavelength of 550 nm are not clearly mentioned, the FoMs have been estimated based on the film thicknesses and the physical appearance of the patterns in comparison to our work.…”
Section: Resultsmentioning
confidence: 99%
“…The reason is attributed to the ultrahigh aspect ratio of the Ag NWs (~1000) used in this work, whereas only short nanowires (aspect ratio < 50) can be used in the reported inkjet printing process. 44,47 Moreover, Ag NW films patterned by our method demonstrates comparable electrical and optical performance to the reported methods, such as photo mask patterning, 43 pattern mask patterning, 42 inkjet printing, 44 micro-contact printing, 41 shadow mask patterning, 53 and magnetic mask printing, 54 as well as other transparent electrodes, such as seed particle printing of metal alloys 55 and laser writing of Ag nanoparticles grid. 10 We thus suggest that our coat-and-print method can take advantage of both coating-based techniques (can lead to patterns with high conductivity and transparency) and printing-based techniques (can efficiently pattern diverse shapes).…”
Section: Resultsmentioning
confidence: 66%
“…Adhesion tests using a standard sticky tape showed partial removal of the NW film, indicating a relatively mild adhesion of the NWs to the polymer substrate that corresponds to van der Waals forces. 24 However, bending tests of the NWdecorated PET substrate demonstrated that the NW film sustained these stringent tests. It therefore appears that while the NW network has relatively weak interactions with PET substrates, it exhibits high resilience against shear forces (see Supporting Information of ref.…”
Section: Resultsmentioning
confidence: 99%
“…This picture is consistent with the observation of resilience of such NW films deposited on PET substrates to bending tests (ref. 24, Supporting Information). Please do not adjust margins…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%